The Growth Drag of Pollution - Andreas Schäfer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Higher child mortality reduces the willingness of parents to invest in children's education and increases their desired level of fertility. In this context, economic inequality is not only decisive for human capital investments and the emergence of differential fertility, but also for agents' exposure to environmental pollution because wealthier households live in cleaner areas. This is the key mechanism through which environmental conditions may impose a growth drag on the economy. In addition, preferred levels of tax-financed abatement measures differ between population groups with different exposures to pollutants, in the sense that the least affected population group prefers the lowest tax rate. Thus, the adverse effect of inequality and pollution on economic growth is amplified, if the population group that is least affected decides about the level of tax-financed abatement measures.
Keywords: O10; Q50; I10; 330